FOSTERING DIGITAL FLUENCY: LIBRARIANS' TACTICS IN BRIDGING THE DIGITAL GAP AND MITIGATING DIGITAL MEMORY LOSS - Novianty Djafri; Hadenan Towpek; Mohd Syahrin (Adisam Publisher, 2024)
Fostering Digital Fluency: Librarians' Tactics in Bridging the Digital Gap and Mitigating Digital Memory Loss